Should family be presence during resuscitation (FPDR)? - Abdul Rahman, Nurul 'Inayati; Aung, Khin Thandar; Nurumal, Mohd. Said; Ahayalimudin, Nurul‘Ain (IOSR journals, 2017)
Background: Nowadays, families expect that they should participate in their own care and decision in health care management. Traditionally, resuscitation is done by health care personnel where family members are excluded from witnessing of this procedure. However, in the last few decades, this idea has been changed into an offering support by allowing family members to be present during resuscitation. The presence of the family members during resuscitation remain controversial. Therefore, there is needed to analysis and argue that some opinions which are associated with the effects of family allowance during resuscitation. Purpose: The purpose of this paper is to discuss the current evidence that the systematic offering of family presence during resuscitation (FPDR) is an ethically sound practice, with minimal demonstrable harms to patients and family members. Methods: By reviewing the related data sources of family presence during resuscitation(FPDR), extensive review of the opinion of family as well as health care providers regarding (FPDR) in CINAL plus, Crossref, Google scholar and research gate. Discussions: This paper will discuss about roles and situation of family during resuscitation, roles and situation of health care providers during resuscitation. Conclusion: FPDR is also a supportive approach to achieve the autonomy of patient and family and reduction the inequalities in health care management.